Mutual absorption of water and essential oils vapours by lignocellulosic material - verification of measured data - Češek, Břetislav; Milichovský, Miloslav; Gojný, Jan (Trans Tech Publications, 2016)
Competitive absorption process, i.e. condensation, of water and essential oils (EO) are predominantly controlled by extent of condensation of diffusing water and EO molecules with marginal influence of porous lignocellulosic matter and a sort of EO. With increase of absorption the diffusion is depressed and vice versa. Diffusion of water molecules through porous system is usually slower in comparison with other molecules. It was discovered, a presence of EO decreases paper web humidity with increasing influence in environment with high relative air humidity. Evaluation of measured values using mathematical growth models, offers an infinite number of solutions for the ratio of water vapour and EO vapour absorption capacities, which in total gives the overall measured absorption capacity. It is necessary to find the right solution. One possibility is e.g. the measurement of water content in the sample after the experiment, or using the methodology described in this paper.
Společná absorpce par vody a esenciálních olejů lignocelulózovými materiály - verifikace naměřených dat
Keywords: lingocellulosic materials; essential oils; porous materials; vapour absorption; lignocelulózové materiály; esenciální oleje; pórovité materiály; absorpce par